Effect of the metabolic inhibitor, methimazole on the drug susceptibility of a triclabendazole-resistant isolate of Fasciola hepatica - Devine, C. (2009)
A study has been carried out to investigate whether the action of triclabendazole (TCBZ) is altered in the presence of a metabolic inhibitor. The flavin monooxygenase system (FMO) was inhibited using methimazole (MTZ) to see whether a TCBZ-resistant isolate could be made more sensitive to TCBZ action. The Oberon TCBZ-resistant and Cullompton TCBZ-sensitive isolates were used for these experiments. The FMO system was inhibited by a 2-h pre-incubation in methimazole (100 m). Flukes were then incubated for a further 22 h in NCTC medium containing either MTZ; MTZ+nicotinamide adenine dinucleotide phosphate (NADPH) (1 nm); MTZ+NADPH+TCBZ (15 g/ml); or MTZ+NADPH+triclabendazole sulphoxide (TCBZ.SO) (15 g/ml). Morphological changes resulting from drug treatment and following metabolic inhibition were assessed using scanning electron microscopy. After treatment with either TCBZ or TCBZ.SO alone, there was greater surface disruption to the triclabendazole-susceptible than -resistant isolate. However, co-incubation with MTZ and TCBZ/TCBZ.SO lead to more severe surface changes to the TCBZ-resistant isolate than with each drug on its own; this was not seen for the TCBZ-susceptible Cullompton isolate. Results of this study support the concept of altered drug metabolism in TCBZ-resistant flukes and this process may play a role in the development of drug resistance.